Predictive factors and psychosocial effects of Internet addictive behaviors in Cypriot adolescents - Critselis, Elena; Janikian, Mari; Paleomilitou, Noni; Oikonomou, Despoina; Kassinopoulos, Marios; Kormas, Georgios; Tsitsika, Artemis K. (My University, 2014)
Background: Internet addictive behaviors are associated with a plethora of psychosocial adversities. The study objectives were to assess the determinants and psychosocial correlates associated with Internet addictive behaviors among adolescents.Materials and methods: A cross-sectional study design was applied among a random sample (n=805) of Cypriot adolescents (mean age: 14.7 years). Self-completed questionnaires, including Internet use characteristics, Young Internet Addiction Test, and Strengths and Difficulties Questionnaire, were utilized.Results: Among the study population, the prevalence rates of borderline addictive Internet use (BIU) and addictive Internet use (AIU) were 18.4% and 2%, respectively. Adolescents with BIU had an increased likelihood of concomitantly presenting with abnormal peer relations (AOR: 5.28; 95% confidence interval, CI: 3.37-23.38), conduct problems (AOR: 4.77; 95% CI: 2.82-8.08), hyperactivity (AOR: 5.58; 95% CI: 2.58-12.10) and emotional symptoms (AOR: 2.85; 95% CI: 1.53-5.32). Adolescent AIU was significantly associated with abnormal conduct (AOR: 22.31; 95% CI: 6.90-72.19), peer problems (AOR: 7.14; 95% CI: 1.36-37.50), emotional symptoms (AOR: 19.06; 95% 6.06-60.61), and hyperactivity (AOR: 9.49, 95% CI: 1.87-48.19). The determinants of BIU and AIU included accessing the Internet for the purposes of retrieving sexual information (AOR: 1.17; 95% CI: 1.17-3.23) and participating in games with monetary awards (AOR: 1.90; 95% CI: 1.15-3.14).Conclusions: Both BIU and AIU were adversely associated with notable behavioral and social maladjustment among adolescents.
Keywords: Addictive behavior; Adolescent; Internet; Problematic Internet use; Psychosocial factors